Penyuluhan kesehatan tentang gizi seimbang pada bayi dan balita - Pribadi, Teguh; Romayati, Umi; Wardiyah, Aryanti; Mu’alifah, Ria; Anjeli, Riri; Ananda, Kiki Erlita (JOURNAL OF Public Health Concerns, 2023)
Introduction: One of the causes of malnutrition and stunting is the behavior and practice of parents in giving food to infants and toddlers that are not good. Good nutritional status of toddlers plays an important role for growth and development, especially during the golden period in the first five years. The results of nutritional status monitoring (PSG) in 2017 in Indonesia showed the prevalence of stunting for toddlers was 27.5%, underweight toddlers 8.0%, very thin toddlers 3.1%, underweight toddlers 22.8% and undernourished toddlers as much as 17.8%. Purpose: To increase mother’s knowledge about the nutritional status of toddlers so that they can reduce the incidence of malnutrition or less than normal toddlers. Method: The method used in this health education is carried out in several stages. The first stage is PSIK students explain about balanced nutrition in infants and toddlers using leaflets and the second after being given public education (respondents) are given a question and answer session about balanced nutrition in infants and toddlers. Results: Respondents (Community) can understand and apply balanced nutrition for infants and toddlers. Conclusion: Respondents (Community) can know and apply the balanced nutrition that should be given to infants and toddlers. Keywords: Balanced Nutrition; Nutritional Status; Toddler Pendahuluan: Salah satu penyebab terjadinya gizi buruk dan stunting yaitu perilaku dan praktek orang tua dalam pemberian makanan pada bayi dan anak yang kurang baik. Status gizi balita yang baik sangat memegang peranan penting bagi pertumbuhan dan perkembangan terutama pada tahap golden period di lima tahun pertama. Hasil Pemantauan Status Gizi (PSG) pada tahun 2017 di Indonesia menunjukkan prevalensi stunting balita sebesar 27,5%, balita kurus 8,0%, balita sangat kurus 3,1%, balita risiko kurus 22,8% dan balita dengan gizi kurang sebanyak 17,8%. Tujuan: Untuk meningkatkan pengetahuan ibu tentang status gizi balita sehingga dapat menurunkan kejadian balita gizi buruk atau kurang dari normal. Metode: Metode yang digunakan dalam penyuluhan kesehatan ini yaitu dilakukan dengan beberapa tahapan. Tahap yang pertama yaitu mahasiswa PSIK menjelaskan tentang gizi seimbang pada bayi dan balita menggunakan lembar leaflet dan yang kedua setelah diberikan penyuluhan, masyarakat (responden) diberikan sesi tanya jawab tentang gizi seimbang pada bayi dan balita. Hasil: Responden (Masyarakat) bisa memahami dan menerapkan tentang gizi seimbang bagi bayi dan balita. Simpulan: Responden (Masyarakat) bisa mengetahui dan menerapkan tentang gizi seimbang yang harus diberikan bagi bayi dan balita.